ПРОБЛЕМА ДУХОВНОСТИ В ТВОРЧЕСТВЕ Ф.С. ФИТЦДЖЕРАЛЬДА И А. АЙЛИСЛИ (Вестник КазНУ. Серия Востоковедения, 2016)
Мақалада автор Ф.С. Фитцджеральд және АкрамАйисли шығармашылығындағы руханият мәселелерінетоқталған.Article is devoted to the problem of spirituality, moralsearches in creativity of F.S.Fitzgerald and Akram Aylisli.The author of article investigates characters of heroes,reveals the lines defining characteristic features ofF.S.Fitzgerald’s and Akram Aylisli’s creativity. Commonfeatures and distinctions in creativity of both authors cometo light.
Keywords: Ф.С. ФИТЦДЖЕРАЛЬДА; А. АЙЛИСЛИ